Strategi Pengembangan Pasar tradisional Kertha, Desa Kesiman Kertalangu, Kecamatan Denpasar Timur - Susanti, IAM. Dwi; Darmawan, Dwi Putra; Astiti, NW. Sri (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2014)
Market competition of traditional and modern markets can be referred to as the global competition. Traditional markets are faced with the modern market of foreign -owned firms in alliance and opened branches in major cities in Indonesia. One is Denpasar city is the provincial capital of Bali. Denpasar city is the center of government, education and the economy. Denpasar city was heavily explore the local culture by revitalizing traditional market presence. Kertha Traditional Market is one of the traditional market located in the Denpasar District East. The purpose of this study to determine the internal and external factors that affect the existence of Kertha Traditional Market, alternative strategies and priorities in the development of strategies Kertha Traditional Market . The study was conducted in Kertha Traditional Market, Kesiman Kertalangu Village, East Denpasar. Determined respondent knowingly, covering people involued in traditional markets, students, and faculty. Internal and external factors were analyzed with analysis of Strength, Weakness, Opportunities and Threat (SWOT) to determine strategic alternatives and analysis Analytic Hierarchy Process (AHP) to determine strategic priorities. The results showed in internal factors, the main strengths is the accessibility and the main weaknesses is the quality of human resources (merchants). In external factors that main opportunities is tourist arrivals and the main threaten is the stability of product prices in the modern market. Alternative strategies are update management strategy Kertha Traditional Market, increase promotion, a partnership between Kertha Traditional Market managers, traders and cooperatives, as well as counseling for the traders.  The main priority of the strategy is "Update Kertha Traditional Market management". Advice given to the manager of the Kertha Traditional Market expected to implement development strategies in priority order, first priority is update traditional market management, both is counseling for the traders, the third is partnership between Traditional Market Kertha managers, traders, and cooperatives, and the fourth is increase promotion Kertha Traditional Market.
Keywords: strategy, traditional market, SWOT, AHP